Care’s Pathways Approach: Kelompok Tani Swadaya Pada Pengelolaan Administrasi Usaha Sawit Berkelanjutan - Heriyanto, Meyzi; Rifai, Ahmad; Fermi, Muhammad Iwan; Ikhsan, Masrul; Vani, Resa Vio (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
As an inclusive movement for independent farmers, who constitute the most dominant actors, accounting for 70% of palm oil plantation management in Riau Province in 2023, and supported by Riau Province's status, holding 23% of the largest palm oil plantation area in Indonesia in 2023. The service method employed is CARE's Pathways Approach, which encourages the capacity building of independent farmers through training and mentoring in more efficient and sustainable plantation administration techniques. By facilitating independent farmers' access to new technologies and innovations, CARE’s Pathways Approach can aid independent palm oil farmers in accelerating their participation in smallholder oil palm replanting, ISPO (Indonesian Sustainable Palm Oil), RSPO (Roundtable on Sustainable Palm Oil), and maximizing efficiency in resource management, particularly in improving plantation administration skills. This includes the use of technology such as electronics, smartphones, email, and other features that can streamline the data collection process, especially for independent palm oil farmer groups, and simplify the process of applying for STDB (Smallholder Palm Oil Plantation Business Registration) and SPPL (Environmental Management and Monitoring Statement) as initial steps toward obtaining sustainable palm oil plantation certification in Indonesia. The findings indicate that Beringin Jaya Village Unit Cooperative (KUD) as the representative of palm oil farmers in Beringin Indah Village has fully participated in the education and socialization processes. This is evidenced by evaluation results showing the capacity and efficiency of this empowerment, which has had a positive impact on the cooperative.